P406 Observational study of the effectiveness of vedolizumab on treatment outcomes and health-related quality of life in biologic-naïve patients with Inflammatory Bowel Diseases in Greece – the TROVE study - Interim Analysis. (30th January 2023) - Chatzinikolaou -, M L; Kifnidi, C; Kokkotis, G; Gatopoulou, A; Michopoulos, S; Soufleris, K; Poulopoulos, G; Theodoropoulou, A; Mantzaris, G; Ntelis, V; Papatheodoridis, G; Tzouvala, M; et al.
Abstract: Background: Vedolizumab (VDZ), a gut-selective anti-lymphocyte trafficking (GSALT), anti-α4b7 integrin antibody, is an approved and effective treatment for patients with Ulcerative Colitis (UC) and Crohn's Disease (CD). Biologic-naïve patients appear to respond better to treatment with VDZ, than anti-TNF exposed patients. Our study aimed to assess the long-term clinical effectiveness and benefit on health-related quality of life (HRQoL) of first line biologic treatment with VDZ in Greek patients with Inflammatory Bowel Disease. Methods: Biologic-naïve patients with moderate to severe UC or CD, received VDZ and were prospectively followed as part of the multicenter observational study TROVE. Interim data were collected between November 2018 and May 2021. The primary endpoint was drug persistence at week 54. Secondary endpoints included clinical response at week 14 [UC&CD, >50% decrease in patient reported outcomes (PRO2)] and clinical remission [UC, partial Mayo score (PMS)<3, PRO2-rectal bleeding=0 and stool frequency=0; CD, PRO2-abdominal pain≤1 and stool frequency≤3) at weeks 14 and 54. HRQoL was assessed using SIBDQ and EQ5D questionnaires. Results: One-hundred and twenty patients from 19 centers were included [Female: 55%, Age (mean): 47.8 years, UC/CD: 56%/44%, Disease duration (median): 2.6 years, Smokers: 25%]. Baseline characteristics are shown in Table 1. At week 54, 72.1% (49/68) of UC patients and 84.6% (44/52) of CD patients continued treatment with VDZ. Among UC patients, clinical remission rates were 60.3% (n=41/68) and 50% (n=34/68) at weeks 14 and 54, respectively. Clinical remission rates for CD were 86.5% (n=45/52) (week 14) and 76.9% (n=40/52) (week 54). At week 14, among UC and CD patients with clinically active disease at baseline, 73.7% (n=42/57) and 83.8% (n=31/37) responded to VDZ treatment, respectively. Among patients who had endoscopy (n=14 UC; n=10 CD), rates of mucosal healing at week 54 were 35.7% for UC (MES 0) and 50% for CD (absence of ulceration) respectively. Non-response at week 14 was associated with higher probability of drug discontinuation at week 54 (OR 3.63; CI 1.19-11.1). Disease duration (<2years vs >5years) did not influence drug persistence at week 54 ( P =0.25). Treatment was intensified in 12.2% of UC and 11.4% of CD patients. The mean increase in SIBDQ and EQ5D between weeks 0 and 54 were 14.6 and 14.4 respectively (for both P <0.001). Conclusion: The majority of UC or CD biologic naive patients remain on VDZ one year after treatment commencement, with high clinical remission rates and improved HRQoL. Clinical response at week 14 predicts long-term drug persistence. Our results support the use VDZ as a first line biologic therapy in IBD patients. The clinical study received funding from Takeda Hellas.